Profil Peternak, Pemanfaatan dan Kualitas Nutrisi Daun Mangrove (Rizophora Apiculata) Sebagai Pakan Hijauan Alternatif Di Kecamatan Tebing Tinggi Barat Kabupaten Kepulauan Meranti - sut trisno (Unpad Press, 2022)
The profile breeder's is a description of person in general depending on which aspect he looks at, starting from age, gender, education and experience influence the use forage in Tebing Tinggi Barat District by utilizing mangrove leaves (Rizophora apiculata) as an alternative feed. The purpose of study was to determine the profile of farmers and the nutritional quality of mangrove leaves (Rizophora apiculata). This research was carried out from March to April 2021 in Tebing Tinggi Barat District and the Laboratory of Nutrition and Feed Technology, Faculty of Agriculture and Animal Science, Sultan Syarif Kasim State Islamic University, Riau. The method used is interview and analysis nutritional quality of mangrove. The results showed that 90% of farmers gave mangrove leaves as forage it can be sean from the age of the highest breeder was 39-50 years, with gender 80% male, and education level 40% high school, and 70% own livestock ownership, had an average of 6-9 goats 55%, farmer occupation 40 %, experience raising more than 5 years 40%, household dependents 1-3 people 71%. Based on the nutritional quality of mangrove leaf meal (Rizophora apiculata) it has 27.62% Dry Matter, 72.37% Moisture water, 6.70% Crude Protein, 13.49% Crude Fiber, 3.33% Crude Fat, 11.65% Ash Content, 64.79% Nitrogen Free Extract ingredient, and 64.93% Total Digestible Nutrient. The conclusion of the study is that farmers are old and do not get information and new innovations and based on proximate analysis of mangrove leaves (Rizophora apiculata) can be used as forage for livestock.Keywords: leaves mangrove, nutritional quality, profile breeder